2016
DOI: 10.1002/gps.4398
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment in a Spanish representative sample: prevalence and associated factors

Abstract: Significant associations between MCI and psychological, cardiovascular and lifestyle factors were found. Targeting modifiable risk factors might reduce the risk for MCI and subsequent dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 44 publications
2
56
4
2
Order By: Relevance
“…52,53 Decline in muscle mass and strength may reduce expression of BDNF that is thought to play a role in brain health. 47,48 61 In the current study, and in accordance with previous publications, 32…”
Section: General Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…52,53 Decline in muscle mass and strength may reduce expression of BDNF that is thought to play a role in brain health. 47,48 61 In the current study, and in accordance with previous publications, 32…”
Section: General Findingssupporting
confidence: 90%
“…The selection of control variables was based on past literature and included age, sex, wealth quintiles based on country-specific income, years of education, physical activity, obesity, number of chronic physical conditions, and depression. 7,32 Physical activity levels were assessed with the Global Physical Activity Questionnaire. 33 The total amount of moderate to vigorous physical activity in a typical week was calculated based on self-report.…”
Section: Control Variablesmentioning
confidence: 99%
“…We applied the same algorithms used in a previous publication to identify MCI [23]. In brief, individuals fulfilling all of the following conditions were considered to have MCI: (a) concern about a change in cognition; (b) objective evidence of impairment in one or more cognitive domains based on a 1-SD cutoff after adjusting for level of education and age of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, dietary patterns may be of great importance in the prevention of cognitive decline in later life (Smith and Blumenthal, 2016). Several studies have indicated the actual benefits of early control of diets and lifestyle in lowering the rate of MCI (Eshkoor et al, 2015; Roberts et al, 2015; Lara et al, 2016). Meanwhile, prospective studies have shown that individuals with a “Mediterranean-like diets” were less likely to suffer from dementia or cognitive decline (Cao et al, 2015; Gardener et al, 2015).…”
Section: Introductionmentioning
confidence: 99%